The Australian RSI epidemic 30 years on - Merdith, Nick (CCH Australia Limited, 2018)
Many of today’s occupational health and safety professionals may not be aware of the unprecedented industrial epidemic that struck Australia in the mid-1980s, and those who were involved may prefer to forget it. Work-related claims for what became known as repetitive strain injuries (RSI) climbed dramatically through the first half of the decade only to decline in the second half. This review revisits the epidemic and its lessons. Although initially blamed on new technology, in particular computer workstations, the epidemic was the result of the complex and interwoven sociotechnological system of health care practice, the compensation and legal system, industrial relations, the media and the social and political environment at the time. There are important lessons we can take from this epidemic that apply to public health practice today, particularly the nocebo effect of negative communications on the beliefs and expectations that can develop within the sociotechnological system.